THE IMPACT OF SOCIAL MEDIA AS A FACILITATOR OF POLITICAL ISSUES IN THE DIGITAL ERA FOR GENERATION Z IN INDONESIA - Aulia, Hanna; Rohman, Miftakhul (SINDA: Comprehensive Journal of Islamic Social Studies, 2024)
One of the reasons for community development in the millennial era is the media. This article discusses the phenomenon that occurs in the era of digitalization which focuses on presence of social media in communication interaction activities. Digitalization has changed in various aspects of life with the presence of social media to aspects of the state including political issues in Indonesia. Social media has the potential to influence power relations in political parties to allowing individual candidates to campaign more independently. What is interesting about this study is how aspects of online media can influence other fields and vice versa. It was found that in the current phenomenon, gen Z are interested in politics, but have not been given the opportunity to become involved in politics.